Interval‐based analysis of pattern distortions in reflector antennas with bump‐like surface deformations. Issue 15 (1st December 2014) - Rocca, Paolo; Manica, Luca; Massa, Andrea
Abstract : The effects on the radiated power pattern of localised defects (also called 'bump‐like surface deformations') in the surface of reflector antennas are studied with an innovative approach based on interval analysis (IA). By exploiting the features of the IA and the rules of the arithmetic for intervals, closed‐form relationships for the bounds (i.e. upper and lower values) of the power pattern are derived once bump‐like deformations with known locations and sizes, but unknown depths, are present. The sensitivity of the nominal power pattern and its features (i.e. sidelobe level, half‐power beamwidth and power peak) are analysed in the case of both single and multiple localised defects. Representative results from several numerical tests concerned with different sizes, locations and number of the surface deformations are reported and discussed to give the interested reader some insights on the capabilities and the effectiveness of the proposed IA‐based approach.